Surgical treatment of the inguinal canal pathology in children - Mladenović Jovan (Praxis Medica, 2018)
Introduction: Hernia is a defect of the continuity of the normal musculoaponeurotic and fascicular abdominal wall, which allows the release of any tissue, except those that normally pass through the apertures on the abdominal wall. Aim: The aim of the paper is to show the frequency of pathological changes in the inguinal region, their timely diagnosis and treatment, in order to avoid the severe consequences of their complications. Material and methods: For this study two-year material of the Surgical Clinical Hospital Clinical Hospital Priština in Gracanica was used, where we analyzed 102 patients who were operated in this center due to pathological changes in the inguinal region. Results: Male males are represented by 91 (89.22%), and female sex with 11 (10.78%) cases. Hernia was recorded in 86 (84.31%) and testicular retention in 16 (15.69%) patients. Femoral hernia in children is extremely rare and occurs in about 0.2% of all hernias of childhood. The femoral hernias on the left with faded and gangrenous left adnex were found in a baby only three months old, where adnectomy was done. Primary hernias was 84 (97.63%) of the patients, while we recorded recurrent hernias in two (2.33%) patients. With one child, we did a recurrent retention of testicles, which was done for a year in another institution. Postoperative complications were reported in one (0.98%) patients, where there was an infection of the wound. Conclusion: In modern surgical practice, it tends to diagnose the hernia at an early stage of development, which facilitates intervention and provides a better postoperative outcome. Incarceration represents a serious complication of all hernias, so timely and accurate diagnosis is needed to take adequate surgical intervention.